Rethinking Evaluation: Alternative Assessment Approaches Used by EFL Teachers at Tribhuvan University - Neupane, Ram Nath (Journal of NELTA Gandaki, 2025)
Alternative assessment moves beyond the limitations of traditional testing by focusing on real-world tasks and student engagement. It provides a more accurate reflection of students' abilities by emphasizing critical thinking and practical application. The present study aims to explore EFL teachers’ perceptions and practices of alternative assessment approaches in Nepalese higher education. To accomplish this, 40 EFL teachers were purposively selected from constituent and affiliated campuses of Tribhuvan University, located in the Gandaki and Lumbini provinces. The teachers were provided a set of questionnaires, comprising both closed-ended and open-ended questions, to collect the intended information. The study reveals that EFL teachers at Tribhuvan University acknowledge the benefits of alternative assessment; however, some key challenges, including limited training, weak ICT skills, and dependence on traditional exams, hinder its implementation. Functional barriers, such as large class sizes, poor attendance, and resistance from stakeholders, further limit adoption. While assessment approaches like portfolios, oral presentations, and digital tools are highly valued, their use remains inconsistent. Effective reform requires clear policies, regular teacher training, improved infrastructure, and enhanced assessment literacy. Promoting collaboration, reducing class sizes, and expanding access to technology alongside pilot programs and stakeholder engagement can support sustainable, student-centered alternative assessment practices across the university.